2018
DOI: 10.1093/femsle/fny136
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of specific bacteriophage against enteropathogenic Escherichia coli (EPEC) and in vitro and in vivo characterization of bacteriophage

Abstract: In recent years, the increasing resistance of enteropathogenic Escherichia coli (EPEC) to commonly used antibiotics has made it difficult to choose the best treatment option. Bacteriophage therapy could be a potent alternative to antibiotic therapy for antibiotic-resistant bacteria. The aim of the present study was to isolate and identify a specific bacteriophage against enteropathogenic E. coli (EPEC) and characterize bacteriophage in vitro and in vivo. The specific bacteriophage was isolated and the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 25 publications
1
19
0
3
Order By: Relevance
“…Ciprofloxacin used as a positive control had a similar protective effect but it did not protect against weight loss. Similar results demonstrating the effectiveness of single doses of phage were obtained by Vahedi et al (2018), who controlled enteropathogenic E. coli in mice, and by Jun et al 2014, who successfully treated mice infected with Vibrio parahaemolyticus (marine bacterium causing infections associated with consumption of raw oysters). Jaiswal et al (2013) also showed that phages administered orally to rabbits by gastric tube 6 and 12 h post-infection controlled V. cholerae infections.…”
Section: Gastrointestinal Tract Infectionssupporting
confidence: 73%
“…Ciprofloxacin used as a positive control had a similar protective effect but it did not protect against weight loss. Similar results demonstrating the effectiveness of single doses of phage were obtained by Vahedi et al (2018), who controlled enteropathogenic E. coli in mice, and by Jun et al 2014, who successfully treated mice infected with Vibrio parahaemolyticus (marine bacterium causing infections associated with consumption of raw oysters). Jaiswal et al (2013) also showed that phages administered orally to rabbits by gastric tube 6 and 12 h post-infection controlled V. cholerae infections.…”
Section: Gastrointestinal Tract Infectionssupporting
confidence: 73%
“…The results of Vahedi et al [119], though positive for phage therapy impact on the treated E. coli mouse gastrointestinal colonization, neither support nor refute compatibility of phage activity with presence of ciprofloxacin. The phage used was not named and treatment doses were delivered orally by gavage.…”
Section: Vahedi Et Al 2018 Escherichia Coli Ciprofloxacinmentioning
confidence: 89%
“…mellonella that are infected with Burkholderia cepacia after treatment with bacteriophages [ 29 ], and other recent studies showed the therapeutic use of E . coli phages against mammalian models [ 30 ]. A simple animal model like wax worm can serve as a tool to determine the initial outcome of the phages in reducing bacterial infections.…”
Section: Resultsmentioning
confidence: 99%